Ceramics from molecular precursors transition metal activation of silicon-carbide precursors - Corriu, Robert; Enders, Markus; Huille, Sylvain; Lutsen, Laurence; Moreau, Joël J. E. (Applications of Organometallic Chemistry in the Preparation and Processing of Advanced Materials, 1995)
Since the early work of Yajima and Verbeck1, a great deal of attention has been devoted to the polymer route to silicon based materials. Efforts have been made to prepare new polymeric precursors with various elemental compositions, with rheological properties allowing to fabricate them into useful forms and also to obtain a better understanding of the ceramisation processes2,3. Whatever is the use of a preceramic polymer: fiber, coating, binder, matrices, it must have at least two important properties which are sometimes difficult to obtain simultaneously. First of all, the polymer must have the appropriate rheology for the fabrication step. Secondly, the elimination of volatile gas must be limited because the yield of residue must be as high as possible and because evolution of gas can damage the ceramic material. Most of the time, this is achieved by adjusting the degree of cross-linking of the preceramic polymer4
Gesehen am 11.11.2022